PENINGKATAN KUALITAS LAYANAN MENGGUNAKAN METODE SERVQUAL (STUDI KASUS DI CV.RAPIH UTAMA JOK PALEMBANG) - Ricky Dermawan Susanto; Theresia Sunami (Jurnal Ilmiah Dinamika Teknik, 2019)
Good service quality is very important in creating customer satisfaction because to understand the expectations of customers, namely security, comfort, speed, timeliness, convenience, and corporate responsibility in handling each service. CV. Rapih Utama Jok Palembang as one of the service providers continues to strive to improve its services so that it can provide excellent service (excellent service). This study uses the ServQual method, where this method identifies five gaps (gaps) that cause dissatisfaction with the implementation of services. Based on the results of processing the ServQual method, obtained several attributes that experience more than 1 gap. Furthermore, several implementations of proposed improvements such as: adding seating facilities, procuring water for consumers, procuring tissue, making procedures for serving consumers, and making rules for serving consumers. There is a gap decrease after implementation of the improvement. The average decrease in gap is 0.355 with an average decrease in percentage of 5.882%.